Implementation of the CLT syllabus in secondary schools in Dhaka, Bangladesh : a study of EFL teachers' classroom practices, knowledge, and skills - Hossain, Muhammad Tofazzel (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study examined the state of EFL teachers' classroom practices at secondary level in Bangladesh. Specifically, it aimed at investigating teachers' understanding of communicative competence, their perceptions towards communicative language teaching, and their classroom practices. To investigate how the EFL teachers implement the CLT syllabus in their classroom practice, this study employed the case study approach. Data were collected through questionnaires, semi-structured open-ended interviews and multiple non-participant observations. The participants were 70 English teachers selected from three secondary schools in Dhaka. The findings indicate that there are some obvious gaps between theory and practice. Furthermore, teachers had mixed perceptions of the effectiveness of CLT. This study also identified the major problems faced by the teachers while teaching English using the communicative approach and displayed the solutions suggested by the teachers along with the suggestions to enhance the teaching of English. The major problems include teachers' quality, teaching materials, methods of teaching, teaching-learning environment, and language assessment system. Additionally, this study explored the teachers' beliefs regarding the most effective ways to teach English to secondary school students in Bangladesh. The teachers suggested alternative ways to teach English effectively to secondary school students in Bangladesh. Based on the findings of this study, implications are provided for the teacher development and the development of the teaching methods in English language teaching at secondary education in Bangladesh.